ANALYSIS OF EXTERNAL STATE DEBT MANAGEMENT THEORY RESEARCH - RAZINKOVA, Mіla (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article develops the theoretical principles of determining the trends in the development of the theory of management of external public debt. The existing studies on the theory of external public debt management are analyzed. In order to implement bibliometric analysis, a number of specialized methods and tools were used (built-in database tools Scopus та Web of Science, VosViewer, Google Trends, Publish or Perish). Considering the large number of scientific works devoted to external public debt, an in-depth cluster analysis was conducted in order to identify the main thematic groups presented in the literature. According to the results of spatial clustering, 6 groups of countries were identified, researchers from which have joint publications on issues of external public debt. On the basis of the bibliometric analysis, key results and general directions regarding the management of the external state debt were determined. The literature on external public debt management traditionally emphasizes debt feasibility, debt thresholds, and the role of fiscal policy in debt management. Recent research has focused on innovative debt management strategies, including contingent liabilities, debt restructuring, and the relationship between debt management and monetary policy. Scholars identify various macroeconomic variables, such as GDP growth, inflation rates, budget deficits, and exchange rates, as the most important determinants of public external debt. The quality of institutions, management structures, and political stability significantly affect the dynamics of external public debt and its management strategy. Researchers have developed concepts and models for assessing the sustainability of external public debt, taking into account such factors as the ratio of debt to GDP, the ratio of debt service to income and external shocks. The literature discusses various debt restructuring mechanisms, such as debt forgiveness, debt extension, and debt buybacks, and their impact on debt sustainability and economic recovery. Research examines the role of international financial institutions, coordination among creditors, and policy interventions in managing external debt crises and promoting sustainable debt restructuring. The literature examines the role of international financial institutions, such as the International Monetary Fund and the World Bank, in providing technical assistance, policy advice and financial support for effective external debt management. Researchers analyze the functioning of sovereign debt markets, including bond issuance, debt securities pricing, secondary market trading, and the impact of market conditions on debt management decisions.
Keywords: debt; external public debt; theories; management; state; research analysis; bibliometric analysis